Classification of factors contributing to high prevalence of occupational accidents at Sino Zimbabwe Cement Company - Samukange, Rumbidzai Carol (Midlands State University, 2017)
The main objective of this study was to investigate the factors contributing to high prevalence of occupational accidents at Sino Zimbabwe Cement Company. Purposive sampling technique was engaged to select the key informants for interviews which included the Finance Manager, SHE officer, Industrial nurse and NSSA factories inspector. The researcher used stratified sampling technique to select 64 respondents for the questionnaires from the target population of 322 employees. The major findings were that accidents at Sino Zimbabwe Cement Company were being largely attributed by job related factors and accidents were mainly due to burns and road traffic accidents. . The causes of such accidents were attributed tolack of adequate training, poor standards procedures and unrealistic production targets. The research revealed that occupational accidents negatively impact cement manufacturing at SZCC due to high rate of lost time; increased absenteeism and frequent stoppage of production operations. The company has introduced strategies to reduce accidents such as Safety talks and monthly plant inspections to raise the awareness level of the accident causation factors among the employees. Measures put in place to reduce accidents which include hazard identification risk assessment, trainings and standard procedures are not effective for accidents and injuries continue to take place The study recommended that employees at SZCC need to attend courses on Occupational, Safety and Health offered by organizations like NSSA so that they would be well versed in Safety, Health and Environment issues. This helps reduce the prevalence of occupational accidents in the organization.